Star polymer/water solutions: new experimental findings - Branca, C.; Magaz, S.; Migliardo, F. (Condensed Matter Physics, 2002)
The purpose of the present work is to highlight a number of recent experimental results that have contributed significantly to the research area of star polymer. Firstly we will refer to a very impressive SANS work by J.Peyrelasse, C.Perreur, J.-P.Habas and J.Franc¸ois which is focused on the study of the structural properties of aqueous solutions of a star copolymer of PEO and PPO by Small Angle Neutron Scattering. Next, we will refer to some experimental advances reported in the work by R.Triolo, V.Arrighi, A.Triolo, P.Migliardo, S.Magaz`u, J.B.McClain, D.Betts, J.M.DeSimone, H.D.Middendorf, which deals with a study of some dynamical properties of PS-b-PFOA aggregates in supercritical CO₂ by Quasi Elastic Neutron Scattering. Метою даної роботи є висвітлення ряду недавніх експериментальних результатів, що зробили значний внесок у фізику зіркових полімерів. Спочатку ми звернемось до дуже вагомої роботи Дж.Пейреласе, С.Перо, Дж.-П.Габас і Дж.Францес, яка присвячена вивченню структурних властивостей водних розчинів зіркових кополімерів PEO і PPO за допомогою розсіяння нейтронів на малих кутах. Далі ми згадаємо деякі експериментальні здобутки, викладені в роботі Р.Тріоло, В.Аріджі, П.Мільярдо, С.Магацу, Дж.Б.МакКлайна, Д.Бетса, Дж.М.ДеСімоне, Г.Д.Мідендорфа, які стосуються вивчення деяких динамічних властивостей агрегатів PS-b-PFOA у надкритичному CO₂ методом квазіпружного розсіяння нейтронів.